PERJANJIAN PERBATASAN WILAYAH NEGARA DALAM PRESPEKTIF HUKUM INTERNASIONAL - Ruthy Kezia Anastasia; Ni Putu Rai Yuliartini (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
In this article discusses the violation of border agreements in the perspective of International Law, the method used is the library method through descriptive presentation and qualitative analysis, which is done by researching library materials such as books, articles and journals related to the object written. . The purpose of writing this article is to provide an understanding of various violations of sovereignty over the territory of the state from the perspective of International Law.